Vendus : a landform of Guinea-Bissau [Resumo] - Alves, Paulo Hagendorn (2019)
ABSTRACT: The Republic of Guinea-Bissau (GB) presents some remarkable geomorphological features such as temporary lakes locally called vendus, meandering rivers, boual / bowal plateaus (hard and dry laterite and bauxite flat surfaces), laterite on successive planation surfaces, collapsed Fe-duricrusts, slope deposits, and finally the Bijagos delta. Vendus are well represented in the 1953 to 1966 old colonial topographic maps scale 1:50,000 and others were identified during fieldwork conducted as part of the edition of the Geological Map of Guinea-Bissau scale 1:400,000 (LNEG and DGGM, as geological surveys of Portugal and GB). These seasonal lakes only occur in the eastern part of the country and the name vendu, a word from the fulbe (fula) dialect, was adopted as this is the main ethnic group on that area.